The Evolutionarily Conserved C-terminal Domains in the Mammalian Retinoblastoma Tumor Suppressor Family Serve as Dual Regulators of Protein Stability and Transcriptional Potency - Sengupta, Satyaki (J Biol Chem, 2015)
The retinoblastoma (RB) tumor suppressor and related family of proteins play critical roles in development through their regulation of genes involved in cell fate. Multiple regulatory pathways impact RB function, including the ubiquitin-proteasome system with deregulated RB destruction frequently associated with pathogenesis. With the current study we explored the mechanisms connecting proteasome-mediated turnover of the RB family to the regulation of repressor activity. We find that steady state levels of all RB family members, RB, p107, and p130, were diminished during embryonic stem cell differentiation concomitant with their target gene acquisition. Proteasome-dependent turnover of the RB family is mediated by distinct and autonomously acting instability elements (IE) located in their C-terminal regulatory domains in a process that is sensitive to cyclin-dependent kinase (CDK4) perturbation. The IE regions include motifs that contribute to E2F-DP transcription factor interaction, and consistently, p107 and p130 repressor potency was reduced by IE deletion. The juxtaposition of degron sequences and E2F interaction motifs appears to be a conserved feature across the RB family, suggesting the potential for repressor ubiquitination and specific target gene regulation. These findings establish a mechanistic link between regulation of RB family repressor potency and the ubiquitin-proteasome system.